Balloon Angioplasty for Embolic Total Occlusion of the Middle Cerebral Artery and Ipsilateral Carotid Stenting in an Acute Stroke Stage - Mori, Takahisa (AJNR Am J Neuroradiol, 1999)
Summary: A 66-year-old man suffering from neurologic symptoms caused by acute embolic total occlusion of the left middle cerebral artery was treated successfully with balloon angioplasty, and an ipsilateral carotid stenosis subsequently was dilated with stenting. The patient's clinical outcome 30 days later was favorable. This therapeutic option may prove to be a useful means of treating a patient with acute stroke, embolic total occlusion of the middle cerebral artery, and an ipsilateral carotid stenosis.